Spint1 disruption in mouse pancreas leads to glucose intolerance and impaired insulin production involving HEPSIN/MAFA - Lin, Hsin-Hsien; Yu, I-Shing; Cheng, Ming-Shan; Chang, Tien-Jyun; Lin, Hsin-Ying; Chang, Yi-Cheng; Ko, Chun-Jung; Chen, Ping-Hung; Lin, Shu-Wha; Huang, Tai-Chung; Huang, Shin-Yi; Chen, Tzu-Yu; et al. (Nature communications, 2024)
SPINT1, a membrane-anchored serine protease inhibitor, regulates cascades of pericellular proteolysis while its tissue-specific functions remain incompletely characterized. In this study, we generate Spint1-lacZ knock-in mice and observe Spint1 expression in embryonic pancreatic epithelium. Pancreas-specific Spint1 disruption significantly diminishes islet size and mass, causing glucose intolerance and downregulation of MAFA and insulin. Mechanistically, the serine protease HEPSIN interacts with SPINT1 in β cells, and Hepsin silencing counteracts the downregulation of Mafa and Ins1 caused by Spint1 depletion. Furthermore, we demonstrate a potential interaction between HEPSIN and GLP1R in β cells. Spint1 silencing or Hepsin overexpression reduces GLP1R-related cyclic AMP levels and Mafa expression. Spint1 -disrupted mice also exhibit a significant reduction in Exendin-4-induced insulin secretion. Moreover, SPINT1 expression increases in islets of prediabetic humans compared to non-prediabetic groups. The results unveil a role for SPINT1 in β cells, modulating glucose homeostasis and insulin production via HEPSIN/MAFA signaling. Pancreatic Spint1 disruption causes glucose intolerance, reduced islet size, and decreased insulin synthesis and secretion. SPINT1 regulates HEPSIN’s modification of GLP1R/MAFA activation, vital for glucose control by β cells, linking it to diabetes.